Simple model for 1/f noise in polycrystalline silicon thin-film transistors - Han, I; Choi, WJ; Kim, HJ; Park, YJ; Cho, WJ; Lee, JI; Chovet, A; Brini, J (KOREAN PHYSICAL SOC, 2003)
We present a simple and novel model for low-frequency excess noise in polycrystalline silicon thin-film transistors. In the model, the grain boundary is considered as a symmetric Schottky barrier and the noise generation mechanisms for both mobility fluctuation and number fluctuation in a Schottky barrier are taken into account. Analysis of the experimental results shows that carrier number fluctuation by barrier height modulation involving thermal activation at bulk trap states in the depletion layer of the grain boundary is found to be responsible for 1/f noise at lower currents. Mobility fluctuation prevails at higher current, due to the increased Hooge parameter and the lack of noise sources for carrier number fluctuation.
Keywords: LOW-FREQUENCY NOISE; SCHOTTKY DIODES; GRAIN; FIELD; LASER; SPECTROSCOPY; FLUCTUATION; CONDUCTION; RESISTORS; PRESSURE